Hints for Genetic and Clinical Differentiation of Adult-Onset Monogenic Autoinflammatory Diseases - Carla Gaggiano; Donato Rigante; Antonio Vitale; Orso Maria Lucherini; Alessandra Fabbiani; Giovanna Capozio; Chiara Marzo; Viviana Gelardi; Salvatore Grosso; Bruno Frediani; Alessandra Renieri; Luca Cantarini (Hindawi Limited, 2019)
Monogenic autoinflammatory diseases (mAIDs) are inherited errors of innate immunity characterized by systemic inflammation recurring with variable frequency and involving the skin, serosal membranes, synovial membranes, joints, the gastrointestinal tube, and/or the central nervous system, with reactive amyloidosis as a potential severe long-term consequence. Although individually uncommon, all mAIDs set up an emerging chapter of internal medicine: recent findings have modified our knowledge regarding mAID pathophysiology and clarified that protean inflammatory symptoms can be variably associated with periodic fevers, depicting multiple specific conditions which usually start in childhood, such as familial Mediterranean fever, tumor necrosis factor receptor-associated periodic syndrome, cryopyrin-associated periodic syndrome, and mevalonate kinase deficiency. There are no evidence-based studies to establish which potential genotype analysis is the most appropriate in adult patients with clinical phenotypes suggestive of mAIDs. This review discusses genetic and clinical hints for an ideal diagnostic approach to mAIDs in adult patients, as their early identification is essential to prompt effective treatment and improve quality of life, and also highlights the most recent developments in the diagnostic work-up for the most frequent hereditary periodic febrile syndromes worldwide.